Current state of existing project risk modeling and analysis methods with focus on fuzzy risk assessment – Literature Review - Pejman Rezakhani (Fracture and Structural Integrity)
Risk modeling and analysis is one of the most important stages in project success. There are manyapproaches for risk assessment and an investigation of existing methods helps in developing new models . Thispaper is an extensive literature survey in risk modeling and analysis methods with main focus on fuzzy riskassessment.